2002
DOI: 10.1038/sj.ejcn.1601394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional assessment techniques in elderly people newly admitted to municipal care

Abstract: Objectives: To evaluate the Subjective Global Assessment (SGA) and the Mini Nutritional Assessment (MNA) with regard to validity using a combination of anthropometric and serum-protein measurements as standard criteria to assess protein-energy malnutrition (PEM). Design: Cross-sectional study with consecutive selection of residents aged ! 65 y. Setting: A municipality in the south of Sweden. Subjects: During a year, starting in October 1996, 148 females and 113 males, aged ! 65 -104 y of age, newly admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
1
20

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 36 publications
7
94
1
20
Order By: Relevance
“…Skin problems, fluid consumption, protein intake and fruits or vegetables intake showed the weakest correlations with the total MNA score. Earlier findings reported similar results, with these items among the questions with the lower correlations (18,36,37) .…”
Section: Discussionsupporting
confidence: 78%
“…Skin problems, fluid consumption, protein intake and fruits or vegetables intake showed the weakest correlations with the total MNA score. Earlier findings reported similar results, with these items among the questions with the lower correlations (18,36,37) .…”
Section: Discussionsupporting
confidence: 78%
“…In various institutional settings, the proportion of the resident population suffering from malnutrition has varied between 15 and 71% and the proportion at risk of malnutrition has been between 40 and 60% (Lauque et al, 2000;Van Nes et al, 2001;Christensson et al, 2002;Gerber et al, 2003). In a Swedish study, 33% of the aged residents living in old people's homes that correspond to our nursing homes suffered from malnutrition (Saletti et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that aged residents living in institutions suffer from malnutrition (Abbasi & Rudman, 1994;Lamy et al, 1999;Lauque et al, 2000;Van Nes et al, 2001;Christensson et al, 2002;Gerber et al, 2003). In Sweden, one-third of aged residents living in old people's homes were malnourished (Saletti et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…MNA has been developed especially for the elderly (Guigoz et al, 1997), and it was recently reported that MNA classification of geriatric patients was related to anthropometric, body composition and functional measurements (Persson et al, 2002). In a comparison between MNA and SGA, MNA was suggested to be most useful in identifying subjects who need preventive nutritional measures, whereas SGA appeared to be better at detecting residents with established malnutrition (Christensson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%